Rabies in Yakutia: Past, Present and Near-Term Prospects - A. D. Botvinkin; I. D. Zarva; A. V. Mel’nikov; A. A. Nikitina; V. F. Chernyavsky (Проблемы особо опасных инфекций, 2025)
The review is based on the results of studying arctic rabies in the tundra and taiga forests of northeastern Russia between 1855 and 2024. The aim of the work was to trace the evolution of scientific knowledge on rabies in Yakutia, to identify the most significant results and prospective areas of research drawing on data accumulated over the observation period. The change of paradigms and priorities at different stages of the study is noted. The spatial-temporal analysis of the rabies spread was carried out through comparing two periods – from the early 21st century and for previous years. Mapping is based on the Natural Earth electronic map in the QGIS 3.2.1 program. Statistical analysis of the dynamics of rabies incidence by years is performed in Rstudio software. Published data on rabies in various animal species are summarized in the table by periods with different diagnostic capabilities. Sporadic human rabies cases in Yakutia (n=6) were identified in 1926 and 1974–1975. Early reports of high rabies incidence in lemmings and detection of the “classical” rabies virus in Yakutia are critically analyzed from the standpoint of modern knowledge. All deposited in GenBank nucleotide sequences of rabies virus genes from Yakutia (n=28) belonged to the arctic genetic line. The relevance of genomic epidemiological surveillance in investigating outbreaks in the central and southern regions of Yakutia is substantiated. The data presented in the review are proposed to be used for planning scientific research and forecasting rabies epizootics in the Arctic.